Media Baru dalam Dinamika Komunikasi Politik pada Era Society 5.0 - Fandhy, Arya; Umam, Khairul; Harahap, Nur Saadah; Nasution, Nurul Adha Almayora (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
This study aims to analyze the role of new media in political communication in the Society 5.0 era, focusing on the effectiveness of digital platforms such as social media in facilitating interaction between politicians and the public. Using a qualitative method with a library research approach, data was collected from various literature and analyzed through Atlas.ti software. The results show that new media plays a central role in building political image, increasing public participation, and enabling more personalized and interactive two-way communication. However, the research also reveals challenges such as societal polarization and disinformation that can affect the quality of democracy. However, social media is considered effective in reaching the younger generation and mobilizing public opinion. This study emphasizes the importance of technological innovation and ethical strategies in utilizing new media to create inclusive and responsive political communication to the needs of society in the digital era.